CagA and VacA Polymorphisms Are Associated with Distinct Pathological Features in Helicobacter pylori-Infected Adults with Peptic Ulcer and Non-Peptic Ulcer Disease - Panayotopoulou, Effrosini G. (American Society for Microbiology (ASM), 2010)
Polymorphic variability in Helicobacter pylori factors CagA and VacA contributes to bacterial virulence. The presence of one CagA EPIYA-C site is an independent risk factor for gastroduodenal ulceration (odds ratio [OR], 4.647; 95% confidence interval [CI], 2.037 to 10.602), while the presence of the vacA i1 allele is a risk factor for increased activity (OR, 5.310; 95% CI, 2.295 to 12.287) and severity of gastritis (OR, 3.862; 95% CI, 1.728 to 8.632).